2015
DOI: 10.1111/1756-185x.12807
|View full text |Cite
|
Sign up to set email alerts
|

The association between initial manifestations of childhood‐onset systemic lupus erythematosus and the survival

Abstract: cSLE survival in Iran was comparable to that in other developing countries. Baseline presentation with hematuria predominantly increased the mortality rate in cSLE. Prospective and larger studies in future may unfold other aspects of cSLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…The prevalence of DAH in cSLE patients in the present study was similar to other reports, varying from 2 to 5% [6,7,24]. Diagnosis of this condition included the typical respiratory symptoms and signs, drop in hemoglobin levels and the radiographic evidence of pulmonary infiltrates, as well as the assessment of hypoxemia due to acute respiratory distress [7].…”
Section: Discussionsupporting
confidence: 88%
“…The prevalence of DAH in cSLE patients in the present study was similar to other reports, varying from 2 to 5% [6,7,24]. Diagnosis of this condition included the typical respiratory symptoms and signs, drop in hemoglobin levels and the radiographic evidence of pulmonary infiltrates, as well as the assessment of hypoxemia due to acute respiratory distress [7].…”
Section: Discussionsupporting
confidence: 88%
“…A few studies showed hematuria to significantly increase the mortality rate in participants with childhood-onset SLE that might have been due to complications associated with the renal organ. [ 38 ] However, other studies have concluded that patients with childhood-onset and adult-onset SLE with renal involvement should both be carefully monitored to prevent unwanted outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately one third of children will present with life-threatening, “non-classical” clinical manifestations that are not included in the revised American College of Rheumatology classification criteria. Fatemi et al [ 15 ] retrospectively studied 188 children, 33 were diagnosed with SLE when they were <12 years, 149 (81.9%) with SLE at 12–18 years of age, 6 patients were lost to follow-up. Both groups had similar clinical manifestations and laboratory findings.…”
Section: Reviewmentioning
confidence: 99%